Bacterium-like particles derived from probiotics: progress, challenges and prospects - Zhou, Xinyao; Gao, Mingchun; De, Xinqi; Sun, Tong; Bai, Zhikun; Luo, Jilong; Wang, Fang; Ge, Junwei (Frontiers in Immunology, 2023)
Bacterium-like particles (BLPs) are hollow peptidoglycan particles obtained from food-grade Lactococcus lactis inactivated by hot acid. With the advantage of easy preparation, high safety, great stability, high loading capacity, and high mucosal delivery efficiency, BLPs can load and display proteins on the surface with the help of protein anchor (PA), making BLPs a proper delivery system. Owning to these features, BLPs are widely used in the development of adjuvants, vaccine carriers, virus/antigens purification, and enzyme immobilization. This review has attempted to gather a full understanding of the technical composition, characteristics, applications. The mechanism by which BLPs induces superior adaptive immune responses is also discussed. Besides, this review tracked the latest developments in the field of BLPs, including Lactobacillus-derived BLPs and novel anchors. Finally, the main limitations and proposed breakthrough points to further enhance the immunogenicity of BLPs vaccines were discussed, providing directions for future research. We hope that further developments in the field of antigen delivery of subunit vaccines or others will benefit from BLPs.